Liposomal form of erlotinib for local inhalation administration and efficiency of its transport to the lungs - Szabová, Jana; Mišík, Ondrej; Fučík, Jan; Mrázová, Kateřina; Mravcová, Ludmila; Elcner, Jakub; Lízal, František; Krzyžánek, Vladislav; Mravec, Filip (International journal of pharmaceutics, 2023)
This contribution is focused on the preparation of a liposomal drug delivery system of erlotinib resisting the nebulization process that could be used for local treatment of non-small-cell lung cancer. Liposomes with different compositions were formulated to reveal their influence on the encapsulation efficiency of erlotinib. An encapsulation efficiency higher than 98 % was achieved for all vesicles containing phosphatidic acid (d ≈ 100 nm, ζ = - 43 mV) even in the presence of polyethylene glycol (d ≈ 150 nm, ζ = - 17 mV) which decreased this value in all other formulas. The three most promising formulations were nebulized by two air-jet and two vibrating mesh nebulizers, and the aerosol deposition in lungs was calculated by tools of computational fluid and particle mechanics. According to the numerical simulations and measurements of liposomal stability, air-jet nebulizers generated larger portion of the aerosol able to penetrate deeper into the lungs, but the delivery is likely to be more efficient when the formulation is administered by Aerogen Solo vibrating mesh nebulizer because of a higher portion of intact vesicles after the nebulization. The leakage of encapsulated drug from liposomes nebulized by this nebulizer was lower than 2 % for all chosen vesicles.
Keywords: nádory plic; Liposome; nemalobuněčný karcinom plic; Lung Neoplasms; Humans; Administration, Inhalation; Carcinoma, Non-Small-Cell Lung; Encapsulation; Liposomes; Aerodynamic particle size; Numerical simulations; Lung; Nebulization; Bronchodilator Agents; erlotinib; Drug Delivery Systems; lidé; nebulizátory a vaporizátory; plíce; velikost částic; Erlotinib Hydrochloride; respirační aerosoly a kapénky; Respiratory Aerosols and Droplets; Non-small-cell lung cancer; lékové transportní systémy; liposomy; aplikace inhalační; Particle Size; bronchodilatancia; Nebulizers and Vaporizers